Biology and systematics of the leafmining Gracillariidae of Brazilian pepper tree, schinus terebinthifolius Raddi, with descriptions of a new genus and four new species) - Davis, Donald R. (2011)
Recent surveys in southern Florida, USA, Brazil and Argentina, for biological control agents to assist in the control of the invasive Brazilian peppertree, have discovered several previously unknown species of plant mining Lepidoptera of the family Gracillariidae. Morphological descriptions with summaries of their biology for the following four new species and one new genus are presented: Caloptilia schinusifolia Davis and Wheeler, from Brazil and possibly Argentina; Eucosmophora schinusivora Davis and Wheeler, from Argentina and Brazil; Leurocephala schinusae Davis and McKay, new genus and species, from Argentina and Brazil; and Marmara habecki Davis, new species, from Florida, USA. The larvae of all four species exhibit a hypermetamorphic development consisting of early instar sapfeeding and later instar tissue feeding stages typical for members of Gracillariidae. Larvae of M. habecki were also observed to possess an additional nonfeeding, transitional instar prior to die final instar as is typical for the genus (Wagner et al. 2000). Larvae of the new genus Leurocephala were discovered to undergo an intermediate, nearly apodal tissue feeding stage between the sapfeeding and final tissue feeding instars. Unique specimens representing an additional three species of Gracillariidae also have been reared from this tree in Argentina or Brazil, but these could not be identified because of inadequate material. COI barcodes were obtained for Marmara habecki, M. smilacisella, and an undescribed Marmara from Brazil. Each species was separated by a minimum barcode divergence of > 4.5% (Fig. 111).